Cost‐savings in hidradenitis suppurativa. (26th April 2019) - Argyropoulou, M.; Kanni, T.; Kyprianou, M.; Melachroinopoulos, N.; Giamarellos‐Bourboulis, E. J.
Summary: Hidradenitis suppurativa (HS) is a common skin disorder that affects almost 1% of people in Europe. HS causes boils to form in areas of the skin with several sweat glands such as the armpit, breast, groin and the buttocks. The disease is characterized by periods in which the symptoms worsen and boils progressively enlarge and rupture with the production of pus and blood. This study, undertaken at the ATTIKON University Hospital of Athens, Greece, focuses on the treatment efficacy of HS with agents that block tumour necrosis factor protein (herein anti‐TNFs). In 2015, one anti‐TNF compound, adalimumab, was licensed for moderate to severe HS. The authors analyzed 250 patients with moderate to severe HS under long‐term follow‐up and they investigated the impact of anti‐TNFs on preventing exacerbations (worsening of the symptoms) and on the cost of treating HS. The authors found that treatment with anti‐TNFs decreased the frequency of exacerbations by 38%; this was achieved both in moderate and severe HS. The authors calculated the cost of patient‐visits separately when under other therapies and separately under treatment with anti‐TNFs. After subtracting the cost of each injection, the authors found that the cost‐saving achieved with anti‐TNFs was €178.92 per visit. The mean year cost for the most severe patients was €8309.6 under other therapies and €3262.2 under anti‐TNFs. These cost findings are for adalimumab, the cost of which was used for the calculations. The results of this study therefore suggest that adalimumab could be a cost‐effective and efficient treatment for HS. Abstract : Linked Article:  Argyropoulou et al. Br J Dermatol 2019; 180 :1161–1168